Analysis of Factors Affecting State Revenue Receipts From the Taxation Sector - Wanti Ernawati; Abdul Aziz; Jaya Mualimin (Journal of Finance and Business Digital, 2022)
State revenues reflected in the APBN can be understood as total state financial revenues. This study aims to describe state revenues from the tax sector. The research method uses explanations from secondary data sources, especially from BPS. The conclusion obtained is that domestic tax revenues sourced from income tax, value added tax and income tax on luxury goods, land and building taxes, excise and other taxes have a direct effect on state financial revenues. The second international trade tax still does not make a significant contribution even though the import duty tax revenue is quite good, and the export tax is still not significant. The contribution of overall tax revenue in Indonesia to state finances is very high.